Molecular characterization of MHC II DRB3 gene of swamp- and riverine-type water buffaloes (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: Major histocompatibility complex (MHC) is a set of molecular proteins on the surface of antigen presenting cells encoded by a large gene family which are important parts of the immune system. This study was conducted to convey information on the genetic characteristics of the MHC II DRB3 gene in riverine and swamp buffaloes.Materials and Methods: Characterization of MHC II DRB3 gene was carried out using polymerase chain reaction (PCR)-based assay. Thirty-milliliter milk samples were collected from 10 swamp-type and 10 riverine-type buffaloes. RNA from milk samples were extracted using Trizol and then followed by reverse transcription-PCR (RT-PCR).Results: The phylogenetic analysis with 1,000 bootstrap replications clearly showed complex parsimony in MHC II DRB3 gene between 10 riverine- and 10 swamp-type but also confirmed that the samples are similar to Bubalus bubalis. Aligned sequences of the 20 water buffaloes were compared with three other ruminants (Bos taurus, Ovis aries, and Capra hircus) and non-ruminant (Sus scrofa) that serve as an outgroup. MHC sequences from GenBank show that there was an average of 705 identical pairs, with 22 transitional pairs and 30 transversional pairs with a ratio of 0.7.Conclusion: Based on the molecular data, the current study conforms to other works of literature that this gene is highly polymorphic which can be due to its function in the immune responsiveness and disease resistance. Further study on the immunological response of MHC II DRB3 to infection may elucidate its underlying function and role in the protection against specific disease of animals.J. Adv. Vet. Anim. Res., 6(3): 308-314, September 2019